THE PERSPECTIVES OF INFORMATION AND COMMUNICATION TECHNOLOGY OF EDUCATION OF STUDENTS IN HIGHER EDUCATIONAL INSTITUTIONS OF UKRAINE - Voronkin О.С. (Journal of Information Technologies in Education (ITE), 2015)
The article presents the results of the expert survey conducted to determine the perspective of development of information and communication technology of education of students in higher educational institutions of Ukraine. The lines of ICT development are forming four generalized sections (organizational, psychological and pedagogical, hardware and software, methodological sections). On the basis of an expert assessment are identified perspectives of 68 lines. The ranking of priority’s lines of development of ICT are presented.It was determined that the greatest prospects will be: blended learning; research teaching method and heuristic teaching method; student-centered approach; increasing the role of informal education; the formation of students’ abilities to independently acquire knowledge; short-term distance learning programs; portable computing devices; the new human machine interfaces; free and open-source software; cloud computing; artificial intelligence technology (search computing with elements of semantics, linguistic systems, decision support system); integrated,multidisciplinary and interdisciplinary training of teachers. Actualized question concerning the need to develop a system of standards in ICT environment.